2019
DOI: 10.1101/697029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of actin protrusion dynamics in cell migration through a degradable viscoelastic extracellular matrix: Insights from a computational model

Abstract: Actin protrusion dynamics plays an important role in the regulation of three-dimensional (3D) cell migration. Cells form protrusions that adhere to the surrounding extracellular matrix (ECM), mechanically probe the ECM and contract in order to displace the cell body. This results in cell migration that can be directed by the mechanical anisotropy of the ECM. However, the subcellular processes that regulate protrusion dynamics in 3D cell migration are difficult to investigate experimentally and therefore not we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…ECs not only migrate in tandem; they also should interact with the avascular regions. These regions are often modelled as matrices with elastic or viscoelastic properties [ 27 , 28 ]; however, the avascular regions also consist of different types of cells that replicate and/or grow. Therefore, an agent-based model for the avascular regions is more appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…ECs not only migrate in tandem; they also should interact with the avascular regions. These regions are often modelled as matrices with elastic or viscoelastic properties [ 27 , 28 ]; however, the avascular regions also consist of different types of cells that replicate and/or grow. Therefore, an agent-based model for the avascular regions is more appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the literature shows that meshless methods converge faster than mesh dependent methods such as the finite element method 17 . Previous works have shown that meshless methods have a good performance in models that analyse great mesh distortion 24 . Nevertheless, the use of these numerical methods to model wound healing angiogenesis has been less explored.…”
Section: Introductionmentioning
confidence: 99%